COST ACCOUNTING: MEMAKNAI BIAYA BONUS DALAM METAFORA SYUKUR - Riska Ismail; Saiful Muchlis; Suhartono Suhartono; Namla Elfa Syariati (Universitas Islam Negeri Alauddin Makassar, 2021)
This study aims to determine the method of determining and accounting treatment for e-commerce bonus fees and to find out a review of the gratitude metaphor for the determination and accounting treatment of e-commerce bonus costs. This study is a qualitative study with a phenomenological approach. Sources of data used are primary data obtained through interviews and observation. The data analysis used is triangulation of data sources consisting of data reduction, data presentation, and drawing conclusions. The results of the study found that in determining the bonus cost, there were several methods such as the use of idle products, based on the profits that had been obtained, based on the acquisition price with a minimum purchase, based on taking parties, and based on certain times. As for the accounting treatment, it varies according to the method used, where the dominant among these methods is measuring based on cost, recognizing it as a cost or profit, and presented in the profit and loss component according to its accumulated value. In the review of the gratitude metaphor, the e-commerce business actors studied have fulfilled three existing elements, namely, being sincere in giving bonuses and the like as a form of gratitude with the heart, saying